Fault Diagnosis of Multistage Manufacturing Processes by Using State Space Approach - Shi, Jianjun; Ceglarek, Dariusz; Jin, Jionghua; Ding, Yu (My University, 2002)
This report presents a methodology for diagnosis of fixture failures in multistage manufacturing processes (MMP).